2014
DOI: 10.1007/s11033-014-3496-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms of glutathione S-transferases and cytochrome P450 enzymes as susceptibility factors to systemic lupus erythematosus in southern Brazilian patients

Abstract: Systemic lupus erythematosus (SLE) is an autoimmune chronic inflammatory disease that presents several clinical manifestations, affecting multiple organs and systems. Immunological, environmental, hormonal and genetic factors may contribute to disease. Genes and proteins involved in metabolism and detoxification of xenobiotics are often used as susceptibility markers to diseases with environmental risk factors. Cytochrome P450 (CYP) enzymes activate the xenobiotic making it more reactive, while the Glutathione… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 62 publications
0
13
0
Order By: Relevance
“…Several studies have suggested that GSTM1 was associated with higher oxidative stress and increased risk for inflammatory diseases, including rheumatoid arthritis [50], systemic lupus erythematosus [51], ulcerative colitis [52], ankylosing spondylitis [5] and inflammatory bowel disease [6]. Several studies have suggested that GSTM1 was associated with higher oxidative stress and increased risk for inflammatory diseases, including rheumatoid arthritis [50], systemic lupus erythematosus [51], ulcerative colitis [52], ankylosing spondylitis [5] and inflammatory bowel disease [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have suggested that GSTM1 was associated with higher oxidative stress and increased risk for inflammatory diseases, including rheumatoid arthritis [50], systemic lupus erythematosus [51], ulcerative colitis [52], ankylosing spondylitis [5] and inflammatory bowel disease [6]. Several studies have suggested that GSTM1 was associated with higher oxidative stress and increased risk for inflammatory diseases, including rheumatoid arthritis [50], systemic lupus erythematosus [51], ulcerative colitis [52], ankylosing spondylitis [5] and inflammatory bowel disease [6].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it is noteworthy that MD patients demonstrated higher levels of GSTM1 transcripts relative to controls. Several studies have suggested that GSTM1 was associated with higher oxidative stress and increased risk for inflammatory diseases, including rheumatoid arthritis [50], systemic lupus erythematosus [51], ulcerative colitis [52], ankylosing spondylitis [5] and inflammatory bowel disease [6]. In addition, the increased frequency of HLA and GSTM1 plays an important role in the alloimmune responses of renal transplant recipients [53].…”
Section: Discussionmentioning
confidence: 99%
“…Only one study is based on the enzymatic level of e-GST in scleroderma [84]. The other studies reported in the literature focused on GSTP1 polymorphisms (see Section 3.6 and Table 1) in pathologies like systemic lupus erythematosus [86], or are meta-analysis suggesting that the GSTP1 polymorphisms are not associated with the risk of rheumatoid arthritis [87]. Another study confirmed the lack of association between GSTP1 polymorphisms and multiple sclerosis [88].…”
Section: Usefulness Of Gstp1-1 Enzymatic Activity In Some Pathologmentioning
confidence: 99%
“…It has been evaluated that the null GSTM1 genotype is present in 40%‐60% of individuals of Caucasian origin, whereas the frequency of the null GSTT1 genotype in the Caucasian population is 10%‐20%. Moreover, carriers of the deletion of both genes ( GSTM1 (‐) and GSTT1 (‐)) account for about 8% …”
Section: Discussionmentioning
confidence: 95%